The The Effect of Vermicompost and NPK Fertilizer on the Growth of Green Mustard (Brassica Juncea L.) - Anggi Yuni Anggraeni; Ahmad Raksun; I Gde Mertha (Jurnal Biologi Tropis, 2022)
Fertilizers are nutrient sources that have a role in determining the growth and production of a plant. Fertilization can be done using organik fertilizers and inorganik fertilizers. The use of combination of organik fertilizers and inorganik fertilizers is carried out to reduce the risk of damage to the soil structure due to the use of inorganik fertilizers continuously. This study aims to determine the effect of applying vermicompost and NPK fertilizers and it’s combinations and know the most effective number of doses of vermicompost and NPK fertilizers for the growth of green mustard plants. The design used is a complete randomized design of 2 factors, namely the dose of vermicompost with 5 levels of doses and doses of NPK fertilizer with 4 levels of each dose in 4 replications. The treatment of vermicompost consisted of 0 gr, 75 ml, 150 ml, 225 ml, and 300 ml. The treatment of NPK fertilizers consisted of 0 gr, 0.4 gr, 0.6 gr, and 0.8 gr/100 ml water. The data were analyzed using ANOVA test. The results showed that the treatment of vermicompost and NPK fertilizers and combination did not have a significant effect on the growth parameters of green mustard plants, namely plant’s height, number of leaves, leaf area, wet weight and dry weight of plant.